Особливості технології виробництва паливних пелет із деревини листяних порід - Червоткіна, Олександра Олександрівна; Chervotkina, Oleksandra; Прокопенко, Олена Павлівна; Prokopenko, Olena; Паляничка, Надія Олександрівна; Palyanychka, Nadiia (Запоріжжя: ТДАТУ, 2025)
UA: У статті розглянуто фізико-механічні властивості паливних пелет, виготовлених із деревини листяних порід. Установлено, що застосування такої сировини без додаткової обробки є малоефективним, оскільки отримані гранули характеризуються недостатньою міцністю. Для усунення цього недоліку вико-ристано попереднє оброблення подрібненої деревини насиченою парою. Проведені промислові випробуван-ня підтвердили, що така активація забезпечує отримання пелет, які відповідають вимогам стандартів якості. Технологічною особливістю процесу є використання матриці з довжиною пресувального каналу 33 мм. /// EN: The article investigates the production technology of fuel pellets from hardwood, focusing on the physical and mechanical properties of the resulting pellets. Hardwood species, such as oak, beech, birch, and ash, are widely used as raw materials due to their availability as by-products of woodworking industries (sawdust, shavings, and chips) and their high calorific value. However, the study reveals that producing pellets from hardwood without additional processing is inefficient, as the pellets often exhibit insufficient mechanical strength and durability. This is primarily due to the lower lignin content in hardwood (19–28% compared to 26–30% in softwood), which acts as a natural binding agent during pelletization, and the higher hardness of hardwood, which complicates the pressing process.To address these challenges, the proposed technology incorporates pre-treatment of the crushed hardwood with saturated steam. This activation process enhances the plasticity of the wood particles, facilitating better bonding during pelletization and improving the structural integrity of the pellets. Industrial tests have demonstrated that steam pre-treatment enables the production of pellets that comply with international quality standards, such as ENplus A1 and A2, which specify requirements for low ash content (0.3–0.5% for debarked hardwood), high calorific value (approximately 5.4 kW·h/kg), and mechanical durability.A key technological feature of the process is the use of a pelletizing matrix with a pressing channel length of 33 mm. This specific matrix design optimizes the compression process, ensuring uniform density and strength of the pellets while minimizing energy consumption and equipment wear. The article also highlights the importance of precise control over the moisture content of the raw material (8–12%) and the removal of bark to reduce ash content, which is critical for producing high-quality pellets suitable for residential and industrial heating systems.The production process involves several stages: sorting and cleaning the raw material to remove impurities, grinding the wood to a fraction of 1–4 mm, drying to achieve optimal moisture levels, steam activation, pelletizing, and cooling. Each stage is tailored to account for the specific properties of hardwood, such as its higher density and hardness compared to softwood. The use of steam activation not only improves pellet quality but also reduces the need for additional binding agents, maintaining the ecological purity of the final product.The resulting pellets are characterized by high energy efficiency, low ash content, and carbon-neutral combustion, making them an environmentally friendly alternative to fossil fuels. They are suitable for use in automated solid-fuel boilers and bioenergy power plants. However, challenges such as higher energy consumption during grinding and pressing, as well as the need for specialized equipment due to the hardness of hardwood, increase production costs compared to pellets made from agricultural residues or softwood.
Features of the technology of production of fuel pellets from hardwood
Keywords: пелети; паливні гранули; деревина; гранулювання; матриця; пресувальний канал; ущільнення; пара; pellets; fuel pellets; wood; pelletizing; matrix; pressing channel; sealing; steam